2003
DOI: 10.1021/jm0204183
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 5-[5-Fluoro-2-oxo-1,2- dihydroindol-(3Z)-ylidenemethyl]-2,4- dimethyl-1H-pyrrole-3-carboxylic Acid (2-Diethylaminoethyl)amide, a Novel Tyrosine Kinase Inhibitor Targeting Vascular Endothelial and Platelet-Derived Growth Factor Receptor Tyrosine Kinase

Abstract: To improve the antitumor properties and optimize the pharmaceutical properties including solubility and protein binding of indolin-2-ones, a number of different basic and weakly basic analogues were designed and synthesized. 5-[5-Fluoro-2-oxo-1,2-dihydroindol-(3Z)-ylidenemethyl]-2,4-dimethyl-1H-pyrrole-3-carboxylic acid (2-diethylaminoethyl)amide (12b or SU11248) has been found to show the best overall profile in terms of potency for the VEGF-R2 and PDGF-Rbeta tyrosine kinase at biochemical and cellular levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
296
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(309 citation statements)
references
References 7 publications
3
296
0
6
Order By: Relevance
“…The anti-cancer drug sunitinib lowers the secretion of cortisol by cultured human NCI-H295 adrenocortical cells, which can be attributed specifically to a decrease in the mRNA and protein expression of HSD3B2 (Kroiss et al 2011). The small molecule sunitinib is a potent multi-targeted receptor tyrosine kinase inhibitor (O'Farrell et al 2003, Sun et al 2003, suggesting that changes in intracellular signaling pathways are able to modulate the HSD3B2 transcription rate. Studies in respectively cultured mesangial cells (Jenkins et al 2000) and osteoblasts (Klein et al 2006) have indicated that exposure to native LDL -the normal substrate of the LDLR -increases the activity (phosphorylation state) of MAPK and tuberin and lowers Src protein levels and Akt activity.…”
Section: Ldlr-ldlr+mentioning
confidence: 99%
“…The anti-cancer drug sunitinib lowers the secretion of cortisol by cultured human NCI-H295 adrenocortical cells, which can be attributed specifically to a decrease in the mRNA and protein expression of HSD3B2 (Kroiss et al 2011). The small molecule sunitinib is a potent multi-targeted receptor tyrosine kinase inhibitor (O'Farrell et al 2003, Sun et al 2003, suggesting that changes in intracellular signaling pathways are able to modulate the HSD3B2 transcription rate. Studies in respectively cultured mesangial cells (Jenkins et al 2000) and osteoblasts (Klein et al 2006) have indicated that exposure to native LDL -the normal substrate of the LDLR -increases the activity (phosphorylation state) of MAPK and tuberin and lowers Src protein levels and Akt activity.…”
Section: Ldlr-ldlr+mentioning
confidence: 99%
“…The precipitated samples were subjected to Western blot analysis as previously described (18). The membrane was sequentially probed with anti-phosphotyrosine (Cell Signaling, Beverly, MA) and anti-FLT3 (Santa Cruz Biotechnology) or anti-PDGFRa (Santa Cruz Biotechnology) antibodies.…”
Section: Reagentsmentioning
confidence: 99%
“…The mTOR inhibitors, rapamycin or its analogue RAD001, have been shown to be active against many types of solid tumors, as well as subsets of leukemia, and are now being used in clinical trials (17). Sunitinib (formerly SU11248) is a novel, orally available, multitargeted receptor tyrosine kinase inhibitor with selectivity against FLT3, c-KIT, PDGFR, and VEGFRs (18). Sunitinib caused regression of various established tumor xenografts derived from human colon, lung, and breast cancers (19).…”
Section: Introductionmentioning
confidence: 99%
“…It is an oral, small molecule with anti-tumor and anti-angiogenic activity that selectively multi-targets inhibition of PDGFR, VEGFR, KIT and FLT3 [74,75]. Recently, the results of two phase 2 trials as second-line therapies in metastatic RCC have been reported.…”
Section: Su11248 (Sunitinib)mentioning
confidence: 99%